Red Blood Cell Distribution Width: A Prognostic Marker in Patients With Type B Aortic Dissection Undergoing Endovascular Aortic Repair - Jiang, Cheng; Liu, Anbang; Huang, Lei; Liu, Quanjun; Liu, Yuan; Geng, Qingshan (Frontiers in Cardiovascular Medicine, 2022)
Background: Red blood cell distribution width (RDW) is associated with cardiovascular mortality. However, the relationship between preoperative RDW and outcomes after thoracic endovascular aortic repair (TEVAR) in type B aortic dissection (TBAD) remains to be determined. Methods: The records of 678 patients with TBAD treated with TEVAR from three centers were reviewed. Patients were divided into two groups according to the admission RDW cut-off by receiver operating characteristic curve analysis: ≤ 13.5% (n = 278) and > 13.5% (n = 400). The association between RDW and long-term mortality was evaluated using Cox survival analysis. Results: Subjects with a high RDW level had significantly higher in-hospital mortality rates (1.4% vs. 4.3%, p = 0.038). A total of 70 subjects died after a median follow-up period of 3.3 years. Kaplan-Meier analysis showed that subjects with RDW > 13.5% had worse survival rates than those with lower RDW values (p < 0.001). Multivariate Cox proportional hazard modeling revealed that an RDW > 13.5% was an independent predictor of long-term mortality (adjusted HR = 2.27, p = 0.006). Conclusion: As an inexpensive and routinely measured parameter, RDW holds promise as a novel prognostic marker in patients with TBAD receiving TEVAR. We found that an RDW > 13.5% at admission was independently associated with increased long-term mortality.